BAHAYA KERJA PENGOLAHAN RSS (RIBBED SMOKE SHEET) MENGGUNAKAN METODE HAZARD IDENTIFICATION AND RISK ASSESSMENT DI PT. PQR - Panjaitan, Nismah (Jurnal Sistem Teknik Industri, 2017)
Occupational Safety and Health is the primary means of prevention of occupational accidents, disabilities and deaths so that the consequences of occupational accidents from potential hazards can be prevented. Companies need to develop risk management based on hazard identification and risk assessment compiled in occupational safety and health programs. Occupational health and safety risk management is an effort of hazard management which potentially pose a risk to safety and health to prevent unwanted accident. The data collected in this research is primary data and secondary data. Primary data obtained through direct observation on the floor processing RSS (Ribbed Smoke Sheet) at PT. PQR is useful to observe the potential hazards of work contained in the work area. While the secondary data taken in this study is historical data. The result of determining the risk value for each hazard source contained in PT. PQR is classified by rankings marked with the code E (extreme risk), H (high risk), M (moderate risk), and L (low risk). This is obtained by comparing the severity and probability values of each process / activity. Of the 28 activities, there are 7 activities included in the category of high risk. Process / activity that belonged to high risk is necessary to control to minimize or even eliminate the existing risks. control measures that can be performed on a high risk process / activity is to use a complete Personal Protective Equipment (APD), MSDS, using warning signs, using ladders in sheet sheets, with ergonomic work posture.Factors causing potential work hazards are workers who perform activities of inadvertent, high temperatures, and negligence of workers in using PPE. These control measures are expected to reduce and even eliminate the risk of the process / activity classified as high risk so that the number of workplace accidents can be reduced.